A Facile Synthesis and Properties of Graphene Oxide-Titanium Dioxide-Iron Oxide as Fenton Catalyst. (26th March 2022) - Jain, Bhawana; Gade, Jaya V.; Hadap, Arti; Ali, Huma; Katubi, Khadijah Mohammedsaleh; Sasikumar, Bashyam; Rawat, Reena
Abstract : Textile industries discharge wastewater in huge amount that contains several toxic contaminants, especially organic dyes. Organic dyes present in wastewater have many adverse effects on environment as well as on living organisms including human beings. The generation of a nanocomposite to trap the toxic organic dyes from wastewater is highly recommended. Herein, we report the preparation of graphene-iron-titanium oxide (GFT) nanocomposite using simple, practical, and cost-effective protocol. The prepared tri-nanocomposite was successfully recognized by employing several analytical techniques. Morphology of the prepared nanocomposites was assessed by SEM coupled with EDS (energy dispersive spectroscopy). HRTEM was used to measure the size of the nanocomposites with shape and morphology. The UV-visible absorption spectra of the nanocomposites were recorded by a UV-visible spectrophotometer. Finally, the crystal structures of the nanocomposites were confirmed by XRD. Moreover, we proposed a plausible mechanism to demonstrate the catalytic activity of GFT oxide nanocomposite for the degradation auramine (AM) dye via a heterogeneous Fenton process.